Microplastic impacts on soil and sediment bioturbation: insights from microcosm experiments across diverse ecosystems - Mohammad Wazne; Franck Gilbert; Manon Vallier; Caroline Lise; Solenn Bailly; Stefan Krause; Laurent Simon; Yvan Capowiez; Florian Mermillod-Blondin; Camille Larue (Environmental Pollution, 2026)

In situ oil contamination in young mangroves: Biodegradation of petroleum hydrocarbons and effects on the microbial and benthic communities, an experimental study in French Guiana - Cécile Militon; Emma Michaud; Léa Sylvi; Lise Millera Ferriz; Enora Roic; Franck Gilbert; Ronan Jézéquel; Philippe Cuny (Marine Pollution Bulletin, 2024)

The burrowing and casting dynamics of earthworms are influenced by litter presence as evidenced by repeated scans and a new marker of bioturbation - Yvan Capowiez; Jean-Marc Bonzom; Nicolas Bottinelli; Franck Gilbert (Applied Soil Ecology, 2024)

Uncovering potential mangrove microbial bioindicators to assess urban and agricultural pressures on Martinique island in the eastern Caribbean Sea - Maud Fiard; Cécile Militon; Léa Sylvi; Jonathan Migeot; Emma Michaud; Ronan Jézéquel; Franck Gilbert; Isabelle Bihannic; Jeremy Devesa; Guillaume Dirberg; Philippe Cuny (Science of The Total Environment, 2024)

Low circulating adropin concentrations predict increased risk of cognitive decline in community-dwelling older adults - Geetika Aggarwal; John E. Morley; Bruno Vellas; Andrew D. Nguyen; Andrew A. Butler; Sophie Guyonnet; Isabelle Carrié; Lauréane Brigitte; Catherine Faisant; Françoise Lala; Julien Delrieu; Hélène Villars; et al. (GeroScience, 2023)
The secreted peptide adropin is highly expressed in human brain tissues and correlates with RNA and proteomic risk indicators for dementia. Here we report that plasma adropin concentrations predict risk for cognitive decline in the Multidomain Alzheimer Preventive Trial (ClinicalTrials.gov Identifier, NCT00672685; mean age 75.8y, SD = 4.5 years, 60.2% female, n = 452). Cognitive ability was evaluated using a composite cognitive score (CCS) that assessed four domains: memory, language, executive function, and orientation. Relationships between plasma adropin concentrations and changes in CCS (∆CCS) were examined using Cox Proportional Hazards Regression, or by grouping into tertiles ranked low to high by adropin values and controlling for age, time between baseline and final visits, baseline CCS, and other risk factors (e.g., education, medication, APOE4 status). Risk of cognitive decline (defined as a ∆CCS of − 0.3 or more) decreased with increasing plasma adropin concentrations (hazard ratio = 0.873, 95% CI 0.780–0.977, P = 0.018). Between adropin tertiles, ∆CCS was significantly different ( P = 0.01; estimated marginal mean ± SE for the 1st to 3rd tertile, − 0.317 ± 0.064; − 0.275 ± 0.063; − 0.042 ± 0.071; n = 133,146, and 130, respectively; P < 0.05 for 1st vs. 2nd and 3rd adropin tertiles). Normalized plasma Aß 42/40 ratio and plasma neurofilament light chain, indicators of neurodegeneration, were significantly different between adropin tertile. These differences were consistent with reduced risk of cognitive decline with higher plasma adropin levels. Overall, these results suggest cognitive decline is reduced in community-dwelling older adults with higher circulating adropin levels. Further studies are needed to determine the underlying causes of the relationship and whether increasing adropin levels can delay cognitive decline.

Are clam-seagrass interactions affected by heatwaves during emersion? - Marta Román; Franck Gilbert; Rosa M. Viejo; Salvador Román; Jesús S. Troncoso; Elsa Vázquez; Celia Olabarria (Marine Environmental Research, 2023)

Biomarkers of mitochondrial dysfunction and inflammaging in older adults and blood pressure variability - Leonardo Bencivenga; Mathilde Strumia; Yves Rolland; Laurent Martinez; Philippe Cestac; Sophie Guyonnet; Sandrine Andrieu; Angelo Parini; Alexandre Lucas; Bruno Vellas; Philipe De Souto Barreto; Laure Rouch; et al. (GeroScience, 2023)

Investigating the combination of plasma amyloid-beta and geroscience biomarkers on the incidence of clinically meaningful cognitive decline in older adults - Wan-Hsuan Lu; Kelly Virecoulon Giudici; John E. Morley; Sophie Guyonnet; Angelo Parini; Geetika Aggarwal; Andrew D. Nguyen; Yan Li; Randall J. Bateman; Bruno Vellas; Philipe de Souto Barreto; Bruno Vellas; et al. (GeroScience, 2022)

Depth distribution of soil organic matter and burrowing activity of earthworms—mesocosm study using X-ray tomography and luminophores - Yvan Capowiez; Franck Gilbert; Audrey Vallat; Jean-Christophe Poggiale; Jean-Marc Bonzom (Biology and Fertility of Soils, 2021)

Effects of the Bioturbating Marine Yabby Trypaea australiensis on Sediment Properties in Sandy Sediments Receiving Mangrove Leaf Litter - Ryan J. K. Dunn; David T. Welsh; Peter R. Teasdale; Franck Gilbert; Jean-Christophe Poggiale; Nathan J. Waltham (Journal of Marine Science and Engineering, 2019)
Laboratory mesocosm incubations were undertaken to investigate the influence of burrowing shrimp Trypaea australiensis (marine yabby) on sediment reworking, physical and chemical sediment characteristics and nutrients in sandy sediments receiving mangrove (Avicennia marina) leaf litter. Mesocosms of sieved, natural T. australiensis inhabited sands, were continually flushed with fresh seawater and pre-incubated for 17 days prior to triplicates being assigned to one of four treatments; sandy sediment (S), sediment + yabbies (S+Y), sediment + leaf litter (organic matter; S+OM) and sediment + yabbies + leaf litter (S+Y+OM) and maintained for 55 days. Mangrove leaf litter was added daily to treatments S+OM and S+Y+OM. Luminophores were added to mesocosms to quantify sediment reworking. Sediment samples were collected after the pre-incubation period from a set of triplicate mesocosms to establish initial conditions prior to the imposition of the treatments and from the treatment mesocosms at the conclusion of the 55-day incubation period. Yabbies demonstrated a clear effect on sediment topography and leaf litter burial through burrow creation and maintenance, creating mounds on the sediment surface ranging in diameter from 3.4 to 12 cm. Within S+Y+OM sediments leaf litter was consistently removed from the surface to sub-surface layers with only 7.5% ± 3.6% of the total mass of leaf detritus added to the mesocosms remaining at the surface at the end of the 55-day incubation period. Yabbies significantly decreased sediment wet-bulk density and increased porosity. Additionally, T. australiensis significantly reduced sediment bio-available ammonium (NH4+bio) concentrations and altered the shape of the concentration depth profile in comparison to the non-bioturbated mesocosms, indicating influences on nutrient cycling and sediment-water fluxes. No significant changes for mean apparent biodiffusion coefficients (Db) and mean biotransport coefficients (r), were found between the bioturbated S+Y and S+Y+OM mesocosms. The findings of this study provide further evidence that T. australiensis is a key-species in shallow intertidal systems playing an important role as an ‘ecosystem engineer’ in soft-bottom habitats by significantly altering physical and chemical structures and biogeochemical function.

RETRACTED ARTICLE: Omega-3 fatty acid levels in red blood cell membranes and physical decline over 3 years: longitudinal data from the MAPT study - Bertrand Fougère; Sabine Goisser; Christelle Cantet; Gaëlle Soriano; Sophie Guyonnet; Philipe De Souto Barreto; Matteo Cesari; Sandrine Andrieu; Bruno Vellas; Bruno Vellas; Sophie Guyonnet; Isabelle Carrié; et al. (GeroScience, 2017)

Bioturbation functional roles associated with mangrove development in French Guiana, South America - Adélaïde Aschenbroich; Emma Michaud; Franck Gilbert; François Fromard; Arthur Alt; Vincent Le Garrec; Isabelle Bihannic; Arnaud De Coninck; Gérard Thouzeau (Hydrobiologia, 2017)

Multistress effects on goldfish (Carassius auratus) behavior and metabolism - Allison Gandar; Séverine Jean; Julie Canal; Nathalie Marty-Gasset; Franck Gilbert; Pascal Laffaille (Environmental Science and Pollution Research, 2016)

Use of dispersant in mudflat oil-contaminated sediment: behavior and effects of dispersed oil on micro- and macrobenthos - Philippe Cuny; Franck Gilbert; Cécile Militon; Georges Stora; Patricia Bonin; Valérie Michotey; Sophie Guasco; Karine Duboscq; Christine Cagnon; Ronan Jézéquel; Cristiana Cravo-Laureau; Robert Duran (Environmental Science and Pollution Research, 2015)

Dynamics of bacterial assemblages and removal of polycyclic aromatic hydrocarbons in oil-contaminated coastal marine sediments subjected to contrasted oxygen regimes - Cécile Militon; Ronan Jézéquel; Franck Gilbert; Yannick Corsellis; Léa Sylvi; Cristiana Cravo-Laureau; Robert Duran; Philippe Cuny (Environmental Science and Pollution Research, 2015)

Effect of physical sediments reworking on hydrocarbon degradation and bacterial community structure in marine coastal sediments - Robert Duran; Patricia Bonin; Ronan Jezequel; Karine Dubosc; Claire Gassie; Fanny Terrisse; Justine Abella; Christine Cagnon; Cecile Militon; Valérie Michotey; Franck Gilbert; Philippe Cuny; et al. (Environmental Science and Pollution Research, 2015)

Oil spill effects on macrofaunal communities and bioturbation of pristine marine sediments (Caleta Valdés, Patagonia, Argentina): experimental evidence of low resistance capacities of benthic systems without history of pollution - Agustina Ferrando; Emilia Gonzalez; Marcos Franco; Marta Commendatore; Marina Nievas; Cécile Militon; Georges Stora; Franck Gilbert; José Luis Esteves; Philippe Cuny (Environmental Science and Pollution Research, 2015)

Functional response of an adapted subtidal macrobenthic community to an oil spill: macrobenthic structure and bioturbation activity over time throughout an 18-month field experiment - Franck Gilbert; Georges Stora; Philippe Cuny (Environmental Science and Pollution Research, 2015)

Quantification of sediment reworking by the Asiatic clam Corbicula fluminea Müller, 1774 - Nabil Majdi; Léa Bardon; Franck Gilbert (Hydrobiologia, 2014)

A cost-effective method to quantify biological surface sediment reworking - Eve De Nadaï-Monoury; Antoine Lecerf; Julie Canal; Laëtitia Buisson; Pascal Laffaille; Franck Gilbert (Hydrobiologia, 2013)

Spatial oxygen heterogeneity in a Hediste diversicolor irrigated burrow - Laura Pischedda; Philippe Cuny; José Luis Esteves; Jean-Christophe Poggiale; Franck Gilbert (Hydrobiologia, 2012)

Spatial mode estimation for functional random fields with application to bioturbation problem - Sophie Dabo-Niang; Anne-Francoise Yao; Laura Pischedda; Philippe Cuny; Franck Gilbert (Stochastic Environmental Research and Risk Assessment, 2010)

Delineation of vine parcels by segmentation of high resolution remote sensed images - Jean Pierre Da Costa; Franck Michelet; Christian Germain; Olivier Lavialle; Gilbert Grenier (Precision Agriculture, 2007)

Hydrocarbon influence on denitrification in bioturbated Mediterranean coastal sediments - Franck Gilbert; Georges Stora; Patricia Bonin; Yveline LeDréau; Gilbert Mille; Jean-Claude Bertrand (Hydrobiologia, 1997)